2018 IEEE 14th International Conference on Control and Automation (ICCA) 2018
DOI: 10.1109/icca.2018.8444304
|View full text |Cite
|
Sign up to set email alerts
|

A Revisit to Gradient-Descent Bearing-Only Formation Control

Abstract: This paper addresses the problem of bearing-only formation control of multi-agent systems, where each agent can merely obtain the relative bearing measurements of their neighbor neighbors whereas relative distance or position measurements are unavailable. In particular, we revisit a bearingonly formation control law proposed in [1]. Unlike many other existing ones, this control law is gradient-descent, which is favorable from the stability analysis point of view. It has the potential to be extended to handle m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 15 publications
0
24
0
Order By: Relevance
“…There have been three approaches describing multi-agent formation, that is, displacementbased formation control, [2][3][4][5][6] distance-based formation control, [7][8][9] and bearing-only formation control. [10][11][12][13] Among the three approaches, distance-based formation control is regarded as a more ideal distributed approach, since the collision between the neighboring agents can be avoided. In the distance-based formation control, graph rigidity was crucial for the formation control, since it could maintain the specified geometry, as discussed in the work by Eren et al 14 It is showed that if the communicated topology graph is rigid, the formation shape could be maintained.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been three approaches describing multi-agent formation, that is, displacementbased formation control, [2][3][4][5][6] distance-based formation control, [7][8][9] and bearing-only formation control. [10][11][12][13] Among the three approaches, distance-based formation control is regarded as a more ideal distributed approach, since the collision between the neighboring agents can be avoided. In the distance-based formation control, graph rigidity was crucial for the formation control, since it could maintain the specified geometry, as discussed in the work by Eren et al 14 It is showed that if the communicated topology graph is rigid, the formation shape could be maintained.…”
Section: Introductionmentioning
confidence: 99%
“…, and the edges in E c are assigned to n À 2 distinct vertices belong to V s in a scalable way via communication. We choose the initialized edge as (1,15; the initialized edge is not unique), and the output of the algorithm is as follows (3,9), (1, 10), (2, 11), (8,12), (4, 13), (7,14), (1,16), (11,17), (9,18), (3,19), (8,20)g 3, 4, 5, 6, 7, 15, 8, 9, 10, 11, 12, f 13, 14, 16, 17, 18, 19, 20g E c = f(3, 2), (4, 3), (5,4), (6,4), (7, 6), (7,15), (8,5), (9,8), (10,3), (11,3), (12,11), (13,11), (14,13), (16,13), (17,12), (18,11), (19,12), (20,…”
mentioning
confidence: 99%
“…Each type of robots is required to maintain on the individual level some constraints relative to members of the other type, i.e., a distance (or bearing) robot is tasked to maintain distance (or bearing) constraints relative to some bearing (or distance) robots within the team. In performing these individual tasks, existing gradient-based control laws in literature [48,53] are implemented. Curious to what collective formation the team may display, we analyze the team consisting of two and three members.…”
Section: Formation Shape Control With Heterogeneous Sensingmentioning
confidence: 99%
“…When the formation shape is specified by inter-robot relative positions [41], then the consensus-based formation control approaches, which are linear, can be used directly. For realizing a formation shape using only distance [23,28], bearing [53], or angle constraints [16], the notion of rigidity [6,16,55] for the underlying interconnection topology is required. The condition of rigidity describes the motions for the whole formation which preserve the formation shape.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation